Equilibrium and Modal Split in a Competitive Highway/Transit System Under Different Road-use Pricing Strategies. (1st January 2014) - Wu, Wen-Xiang; Huang, Hai-Jun
Considering body congestion in carriage and vehicle congestion in bottleneck queues in a competitive highway/transit system, we investigate the departure patterns of commuters through analysing the equilibria under three road-use pricing strategies. Each strategy is the combination of a time-varying toll and a flat toll. We find that the flat toll for minimising total social cost is negative and financial subsidy is needed to encourage some commuters to leave home earlier or later. A positive flat toll, for maximising the highway owner's profit, leads to shortening and extension of the departure time intervals using auto and transit modes, respectively.